French historians in the nineteenth century : providence and history - Holthoon, F. L. van (Cambridge Scholars Publishing, 2019)
This study is a reflection on the major historians of nineteenth-century France, and shows that, near the end of the century, a major change of perspective occurred. The historians discussed in the opening sections of the book looked to the past for guidance, while modern historians from the twentieth-century onwards regard the past as a closed book which the historian has to open. Guizot is the hero of the first section of the book; in part two, Comtesse d'Agoult (Daniel Stern) is specifically mentioned, partly because she, who wrote a splendid history of the revolution of 1848, tends to be ignored as a historian while Michelet and Tocqueville are still discussed. The historians in part three are transitional figures who politically and morally still belong to the nineteenth-century, but whose histories show the new approach to the past.